Microwave-modified xanthan gum: Alterations in steady and dynamic rheological behaviors - Kurt, Abdullah; Ozturk, Eylul; Ozmen, Duygu; Yildirim-Yalcin, Meral; Arici, Muhammet; Toker, Omer Said (WILEY, 2024)
In this study, microwave modification of xanthan gum (XG) powder under various power and time settings was aimed at achieving diversity for different applications requiring different flow behaviors. Microwave treatment for 6 min at various powers showed no noticeable effect on the properties of XG. The apparent viscosity, consistency coefficient and viscoelastic properties (G '-G '') increased as powders were subjected to microwave treatment for up to 8 min and the highest increase was observed in XGs with 720 W application. The increasing power to 1200 W resulted in a decrease in consistency at 8 min. At all levels of power, a prolonged microwave treatment (10 min) resulted in the degradation of the molecules, leading to a decrease in the mentioned rheological properties of XG. The values for intercepts (K ' and K '') began to increase at 960 W-6 min, with the largest increase occurring at 720 W-8 min. Fourier transform infrared (FTIR) analysis revealed that the primary structure and repeated units were not negatively impacted by the use of microwave treatment. Therefore, with adjustable modification, microwaves may be employed to produce xanthan gum with a high economic value that is suitable for a variety of applications, while maintaining the gum's color properties.Practical applicationsOur research demonstrated that the use of microwave technology as a non-thermal physical process to modify xanthan gum powder without dissolving it in water is a highly effective technique. This approach enables the flow characteristics of xanthan gum to be conveniently modified, regardless of its concentration, and increases its economic value by diversifying its techno-functional properties. The increase in apparent viscosity and viscoelastic properties by increasing the interaction of polymer molecules or the adaptation of xanthan gum to different purposes by polymer degradation can be adjusted depending on the power and time of the microwave. Microwave modification was carried out on xanthan gum (XG) powders. The highest viscosity and viscoelasticity were measured at 720 W-6 min. The rheological properties decreased after 10-min microwave treatment. The main structure of XG was not adversely affected by microwave. Microwaves are suitable for the production of functional XG, regardless of concentration.image
Keywords: microwave treatment; modification; rheological properties; xanthan gum; LEPIDIUM-SATIVUM GUM; DEGRADATION; HYDROGELS; GUAR; Engineering; Food Science & Technology